The Development of Early Adolescent Food and Nutrition Literacy Model in Southern Thailand - Yodrak, Wanlee; Choeibuakaew, Wallapa; Saithanoo, Somkiat; Vanaleesin, Srisuda (Health Science Journal of Thailand, 2025)
This mixed-method research aimed to 1) develop a conceptual framework for food and nutrition literacy among early adolescents1 and 2) construct a model for food and nutrition literacy in this population. The study was conducted in three phases. In the first phase, the conceptual framework was built through in-depth interviews with nine experts in health literacy, nutrition, and adolescence (IOC = 0.80–1.00) and a concept analysis review of 22 relevant literature sources. Phase 2 focused on constructing a preliminary model using quantitative research with a sample of 500 Grade 7 students in Phatthalung province. Data were collected via questionnaires (IOC = 0.80–1.00; Cronbach's alpha = 0.92) and analyzed using exploratory factor analysis. Phase 3 refined and validated the model through confirmatory factor analysis with a stratified random sample of 1,000 Grade 7 students from southern Thailand. The findings revealed that: 1) the conceptual framework consisted of three levels and six components; 2) food and nutrition literacy in early adolescents comprised six components; and 3) the final model had five components aligned with empirical data (χ² = 1842.29, df = 522, χ²/df = 3.529, p-value < 0.001). This study provides a robust framework and model for understanding food and nutrition literacy, serving as a foundation for promoting the health of early adolescents effectively.